The Change of Religious Understanding from Ideal-Rationality to Pragmatic-Materialistic - Ishomuddin Ishomuddin (UIN Maulana Malik Ibrahim Malang, 2017)
The study is conducted because of the appearance of many new beliefs in Islam, which has had considerable influence for Indonesian Muslims, regardless the fact that the beliefs have mostly been classified as a cult. The purposes of this study are to investigate the new phenomenon in the religious act, involving the change of understanding from ideals-rationality view to pragmatic-materialistic view, and to focus on the phenomenon of the emergence of new faiths in Islamic society in Indonesia. This study is aimed to answer the following questions: (1) What motives lie behind the change of religious understanding from ideals-rationality view to pragmatic-materialistic view in today's Muslim group?; (2) How does the changing process of religious understanding occur in the Muslim group?; (3) Why do religious people today tend to be pragmatic-materialistic oriented and leave the religious teachings that have been previously understood? Qualitative approach is used to examine the research questions. The research result shows that there are three kinds of typology of Muslim groups which experience a shift in religious understanding from ideality-rationality belief to pragmatic-materialistic belief. This happens because there is a gap between the quality of faith and the desire to become instantly rich. Penelitian ini dilakukan untuk mendeskripsikan dan memahami gejala new act dalam beragama yaitu fenomena pergeseran pemahaman spiritual dari idealitas-rasionalitas ke pragmatis-materialistis dalam beragama. Penelitian ini difokuskan pada fenomena munculnya kelompok-kelompok atau aliran-aliran baru dalam masyarakat Islam di Indonesia. Secara rinci penelitian ini adalah untuk menjawab pertanyaan-pertanyan berikut ini. Apa yang melatarbelakangi adanya perubahan pemahaman agama dari idealitas-rasionalitas ke pragmatismaterialistis dalam beragama masyarakat sekarang ini? Bagaimana proses perubahan keberagamaan itu terjadi pada masyarakat Islam? Mengapa umat beragama sekarang ini cenderung kepada pemahaman agama secara pragmatismaterialistis sehingga kehilangan orientasi dan meninggalkan ajaran-ajaran agama yang telah dipahami sebelumnya? Penelitian ini menggunakan pendekatan kualitatif. Berdasarkan analisis data terdapat tiga macam tipologi kelompok muslim yang mengalami pergeseran pemahaman agama dari idealitas-rasionalitas ke pragmatis-materialistis. Hal ini terjadi karena adanya kesenjangan antara kualitas keimanan dengan keinginan untuk menjadi kaya secara instan.